Case Report of a Traumatic Atlantoaxial Rotatory Subluxation with Bilateral Locked Cervical Facets: Management, Treatment, and Outcome - Nael Hawi; Dirk Alfke; Emmanouil Liodakis; Mohamed Omar; Christian Krettek; Christian Walter Müller; Rupert Meller (Case Reports in Orthopedics)
The aim was to report a rare case of isolated traumatic atlantoaxial rotatory subluxation without ligamentous injury. Management consisted of analgesia, sedation, and application of a halo skull traction device. After removing halo skull traction, full reduction and recovery were achieved without instability.